O5.1. STRIATAL DOPAMINE AND REDUCED REWARD PREDICTION ERROR SIGNALING IN UNMEDICATED SCHIZOPHRENIA PATIENTS. (18th May 2020) - Katthagen, Teresa; Kaminski, Jakob; Heinz, Andreas; Buchert, Ralph; Schlagenhauf, Florian
Abstract: Background: Increased striatal dopamine synthesis capacity (DSC) has consistently been reported in patients with schizophrenia (Sz). However, the functional mechanism translating this into behavior and symptoms remains unclear. It has been proposed that heightened striatal dopamine may blunt dopaminergic reward prediction error (RPE) signaling during reinforcement learning. Methods: In this study, we investigated striatal DSC and RPEs and their association in unmedicated Sz and healthy controls. 23 healthy controls (HC) and 20 unmedicated Sz took part in an FDOPA-PET scan measuring DSC and underwent fMRI scanning, where they performed a reversal learning paradigm. We compared groups regarding DSC und neural RPE signals and probed the respective correlation (23 HC and 16 Sz for both measures). Results: There was no significant difference between HC and Sz in DSC. Taking into account comorbid alcohol abuse revealed that only patients without such abuse showed elevated DSC in the associative and sensorimotor striatum, while those with abuse did not differ from HC. Patients performed worse during learning, accompanied by a reduced RPE signal in the ventral striatum. In HC, the DSC in the limbic striatum correlated with higher RPE signaling, while there was no significant association in patients. DSC in the associative striatum correlated with higher positive symptoms, and blunted RPE signaling was associated with negative symptoms. Discussion: Our results suggest that dopamine modulation of RPE is impaired in schizophrenia. Furthermore, we observed a dissociation with elevated DSC in the associative and sensorimotor striatum contributing to positive symptoms and blunted RPE in the ventral striatum to negative symptoms.